PAIN AND INFLAMMATION. PART 1. PATHOGENETIC ASPECTS - A. E. Karateev; D. E. Karateev; O. S. Davydov (Научно-практическая ревматология)
The relief of suffering, which is associated with a rapid and complete elimination of painful sensations, is the most important challenge facing physicians of many specialties. It is obvious that it can be solved only when you understand clearly the processes governing the development and chronization of pain. Inflammation, a universal adaptive mechanism that always accompanies damage to living tissues, plays a key role. Part 1 of this review considers the main stages of development of an inflammatory response, beginning with primary damage accompanied by the release of molecules acting as an alarm and ending with the deployment of a complete picture of the inflammatory response with the involvement of many cell elements and the overexpression of cytokines and proinflammatory mediators. The biological basis of the peripheral and central nociceptive sensitization phenomenon that is rigidly associated with inflammation is presented. Particular emphasis is placed on the possible natural completion of the inflammatory response, on the adaptive mechanisms regulating this process and on the reasons that prevent this and determines inflammation chronization.